KEPASTIAN HUKUM PUTUSAN PENGESAHAN HOMOLOGASI DALAM PERKARA KEPAILITAN - Zahra Athirah (Warmadewa University Press, 2023)
Ratification of the peace agreement issued by the Commercial Court result in the peace agreement being executed being binding between the parties and legally enforceable. Every case that has been decided by the Panel of Judges in court must of course contain aspects of justice, legal certainty and expediency. In its implementation, it is not easy to realize these three aspects, especially the aspect of legal certainty. Legal certainty can be realized if every legal substance conforms to the norms or needs of society. This means that the law can provide legal certainty that can reflect the culture and origins of that society. This research aims to analyze the legal certainty of peace decisions (homologation) related to PKPU in bankruptcy cases and their legal consequences. The research method used is normative juridical with an approach through legislation. The data source used is a secondary data source. The results of this research show that there is legal uncertainty in the decision to cancel a peace agreement because an agreement that has been ratified should not be able to be canceled and the implementation of the cancellation of the agreement that has been ratified has legal consequences for both debtors and creditors. The legal consequence is that the peace agreement that has been ratified is deemed to have never occurred and is null and void. The debtor was declared bankrupt again because he was considered negligent in fulfilling his obligations in paying debts that were due based on the agreed agreement. For creditors, the debtor's bankruptcy assets are divided among creditors in various ways based on Article 176 of Law no. 37 of 2004. The conclusion and suggestion in this research is that there should be regulations regarding further provisions regarding the cancellation of peace agreements in order to create legal certainty.